A quantitative experimental study of wetting hysteresis on discrete and continuous chemical heterogeneities - Priest, C.; Sedev, Rossen; Ralston, J. (2013)
Chemically heterogeneous surfaces are well known to induce contact angle hysteresis due to the local energy barriers that oppose contact line movement. In many cases, the surface heterogeneity is discontinuous, i.e. discrete regions of different wettability exist, which leads to pinning of the contact line at boundaries between regions. Pinning on individual rows of microscopic defects arranged in a square lattice can be sensed using a Wilhelmy balance to reveal discrete stick-slip motion. For defects more wettable than the matrix with a lattice spacing of 28 µm, the advancing contact line slips over ~10 rows in a single slip step, while the receding contact line stick-slips between individual rows of defects. Single, millimetre-scale defects were used to assess the energy involved when a contact line advances or recedes over a hydrophilic (more wettable) defect. Quantitative information about defect-induced hysteresis in relation to defect dimensions is obtained. The crucial importance of wetting boundaries is highlighted with an experimental example of a surface that is heterogeneous yet, due to the continuously changing pattern, does not exhibit contact angle hysteresis.